El Excentrico, 1955-02-20 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
February 20, 1955 [20 de febrero de 1955]. Ano 5, No 8. Cover has a photo of young Linda Caudillo in a formal gown with headline reading, "Graceful future young Miss."